Peran Orang Tua dalam Menghadapi Sekolah Anak Berkebutuhan Khusus (ABK) di TK Negeri Pembina Kota Gorontalo - Syafna A. Tahir; Rizkiyastuti Abd. Malik; Salsabila Puluhulawa (ICHIGO : Jurnal Bahasa, Sastra, Pendidikan, dan Budaya Jepang, 2024)
Children with Special Needs (ABK) require different attention, approaches, and educational strategies compared to children in general. In the process of ABK education, the role of parents is an important factor that influences the success of learning and child development. This article aims to examine the role of parents in dealing with and accompanying children with special needs during their education at school. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies of several ABK parents. The results of the study indicate that parents have a role as companions, motivators, facilitators, and partners in collaboration with the school. In addition, the challenges faced by parents include lack of information about inclusive education, economic limitations, and psychological burdens. These findings emphasize the importance of support from schools and the government, such as counseling, training, and access to special services, to empower parents in optimally accompanying the education of ABK children.